PENGARUH STRES KERJA DAN KUALITAS KERJA TERHADAP KINERJA KURIR DOKUMEN (STUDI KASUS JASA PENGIRIMAN PT. PRIMA MULTI CIPTA, JAKARTA SELATAN) - Venty Melani; Agus Sudigdo (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2020)
This study aims to determine whether there is an influence of work stress and employee work quality on the performance of the courier at PT. Prima Multi Cipta South Jakarta branch. This research was conducted in August 2019 through the help of a questionnaire. The population in this study is the Courier PT. Prima Multi Cipta. Research power was obtained through a questionnaire about Stress and employee work quality to 50 respondents. The instrument testing method used is validity and reliability testing. The data analysis technique used is quantitative descriptive technique, multiple linear regression analysis and t test. Based on the results of the discussion outlined, it was concluded that there was a significant difference between work stress and performance. There is a positive and significant effect between employee work quality on performance.Keywords: Job stress, Work Qualilty, Performance